Estudio de factibilidad para la implementación de un campamento vacacional para niños, niñas y adolescentes de 6 a 16 años de edad en la parroquia la matriz de la ciudad de Guano provincia de Chimborazo - Aulla Arguello, Glenda María (2015)
This thesis project entitled "Feasibility study for the implementation of a summer camp for children and adolescents 6-16 years of age in the parish Matrix City Guano Chimborazo province," emerged as a necessity to take advantage of the great attractions on the area of the matrix parish, as a place that provides all the components to create a summer camp for children Guano city, the province and even the country. Among the goals they had set for this research project they were: General objective: Develop a feasibility study for implementation of a summer camp for children and adolescents 6-16 years of age in the parish Matrix City Guano Chimborazo province. Specificobjectives: 1. Perform a market research where potential demand real and effective is determined, unmet. 2. Set in the technical study the size and location of the project and the engineering of it. 3. To establish legal and administrative organization in the company. 4. Establishthefinancialstudy. 5. Define the economic feasibility of the project using financial evaluation indices such as NPV, IRR, RB / C, PRC, AN / Sc to meet profitability through technical formulas evaluate the results, to meet the project's profitability. 6. Bibliography, direct observation, directed to the sample of the population of the city of the province of Chimborazo Guano surveys: techniques as applied. Scientific, inductive, deductive, descriptive, analytical and mathematical: methods such as was used. As a final product the current situation of the sector and the province Canton was obtained. Market Study on implementing a Holiday Camp was established, because there is an unmet demand for services to cover 48,913 a year. The Technical Study, installed capacity for the services provided Camp 2,400 annual rental services, which will increase over the life of the project, starting with a capacity utilization of 85% for the first year was determined. In the Management Study type Holiday Camp, which is to be constituted as a limited liability company, under the name Holiday Camp "The CIA was defined Labrador. LTDA., "Was also established that has developed charts at different hierarchical levels and functions should play each of them also it features a manual was developed for staff. Project costs by giving us a $ $ 47,645.80 described in the Economic Survey. It will be financed by a credit of $ 20,000.00 to 12% annually and cover it difference of capital project partners. Financial Performance in the profit and loss account where it was determined that the net income for the first year is $ 15,353.76 was analyzed, and the cash that has the Recreation Center to cover its operations through cash flow was also determined. Finally in the criteria for evaluating the project's NPV of $ 48,008.40 that it exceeds the initial investment for which the project is considered feasible it was determined. The IRR is 32.23%, this was higher than the rate of interest canceling financial identities. In the sensitivity analysis of costs it increased 10.28% and decreased revenues 8.55% indicates that the project is not sensitive. With reference to RBC is $ 1.20 which means that for every dollar invested the project will have a profit of $ 0.20 cents for services; and the project investment is recovered in two years, two months and 26 days